2017
DOI: 10.1080/20002297.2017.1385372
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of genes TEC1 and EFG1 in Candida albicans influences extracellular matrix composition and biofilm morphology

Abstract: Background: Infections caused by Candida spp. have been associated with formation of a biofilm, i.e. a complex microstructure of cells adhering to a surface and embedded within an extracellular matrix (ECM). Methods: The ECMs of a wild-type (WT, SN425) and two Candida albicans mutant strains, Δ/Δ tec1 (CJN2330) and Δ/Δ efg1 (CJN2302), were evaluated. Colony-forming units (cfu), total biomass (mg), water-soluble polysaccharides (WSPs), alkali-soluble polysaccharides (ASPs), proteins (insoluble part of biofilms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…in C. glabrata biofilms), all biofilms released comparable amounts of eDNA both in presence or absence of FLZ. This result corroborates to a previous finding that observed that a strain defective in hyphae formation (Δ/Δ efg1) was capable of producing eDNA similar to its parental strains that formed hyphae [35]. In C. albicans , eDNA contributes to the preservation and stability of mature biofilms, but not to their establishment [24,25], while the recognized role of some proteins is linked to metabolism [26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…in C. glabrata biofilms), all biofilms released comparable amounts of eDNA both in presence or absence of FLZ. This result corroborates to a previous finding that observed that a strain defective in hyphae formation (Δ/Δ efg1) was capable of producing eDNA similar to its parental strains that formed hyphae [35]. In C. albicans , eDNA contributes to the preservation and stability of mature biofilms, but not to their establishment [24,25], while the recognized role of some proteins is linked to metabolism [26].…”
Section: Discussionsupporting
confidence: 89%
“…Biofilm formation and processing for Log 10  CFU/mL, total biomass, insoluble biomass, proteins (from the insoluble part of the biofilm and from the supernatant), alkali-soluble polysaccharide (ASP), water-soluble polysaccharide (WSP), and eDNA were performed according to the methodology described by Panariello et al [35]. Briefly, biofilms of CaS, CaR, CgS, and CgR were developed for 48 h in RPMI buffered with MOPS (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Although in C. glabrata very little is known about the regulation of biofilm formation, in C. albicans one of the major regulators of biofilm formation is CaTec1 transcription factor (Schweizer et al, 2000;Nobile et al, 2012;Daniels et al, 2015;Panariello et al, 2017). The deletion mutant of the predicted ortholog of CaTec1 in C. glabrata, encoded by ORF CAGL0M01716g and here named CgTec1, was used to assess its possible role controlling the expression of these MFS transporters during early (6 h) and mature (24 h) stages of biofilm formation.…”
Section: Cgtec1 Transcription Factor Controls the Expression Of Cgqdrmentioning
confidence: 99%
“…), like the enhanced filamentous growth transcriptional factor ( EFG1 ), a well‐characterized major activator of hyphal development (Panariello et al . ), the z inc‐responsive activator protein (Zap1) that governs the balance of yeast and hyphal cells in biofilms (Ganguly et al . ), the agglutinin‐like sequence ( ALS ) gene family notably the cell wall glycoproteins Als3p, the hyphae‐specific genes like hyphal wall protein (Hwp1) and the extent of cell elongation 1 protein (Ece1) (Nobile et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we sought to further investigate the cellular and molecular mechanisms supporting the SV extract inhibition of C. albicans biofilm. Particularly, we focused on the effect of the SV extract on the expression of several key transcriptions factors that control a network of target genes involved in C. albicans biofilm (Kumamoto and Vinces 2005;Fanning et al 2012;Nobile et al 2012), like the enhanced filamentous growth transcriptional factor (EFG1), a well-characterized major activator of hyphal development (Panariello et al 2017), the zinc-responsive activator protein (Zap1) that governs the balance of yeast and hyphal cells in biofilms (Ganguly et al 2011), the agglutinin-like sequence (ALS) gene family notably the cell wall glycoproteins Als3p, the hyphaespecific genes like hyphal wall protein (Hwp1) and the extent of cell elongation 1 protein (Ece1) (Nobile et al 2006;Ding et al 2014). Moreover, we also investigated effect of SV extract on expression of the hyphal G cyclin 1 (HGC1) that is activated by hyphae-inducing signals (Zheng et al 2004;Fan et al 2013) and of the secreted aspartyl proteinases (SAPs) that are major virulence factors mainly regulated by the cell morphotype and the environmental factors (Theberge et al 2013;Kumar et al 2015).…”
Section: Introductionmentioning
confidence: 99%